Pitch-derived P-doped carbon/GeP3 composite via ball milling towards enhanced sodium-ion storage - Kewei Shu; Cunguo Yang; Huizhu Niu; Xiaorui Fuyan; Shuqi Yang; Haihua Wang (Electrochemistry Communications, 2024)
GeP3 is a promising anode material for sodium ion battery due to better conductivity, relatively high theoretical capacity and improved mechanical endurance compared to phosphorus and other phosphides. However unsatisfied rate capability and cycling stability is still an annoying issue that hinders the application of GeP3. Here, GeP3 was hybridized with P doped carbon (PPC) derived from low-cost coal tar pitch to prepare composite electrode. Through ball-milling process, the GeP3 and PPC was homogenously mixed and form fused, secondary particles as confirmed by electron microscope. The formation of P-C and P-O-C bond between GeP3 and carbon matrix was evidenced by XPS, and prompted by P doping level and O content in PPC. The electrochemical performance of the composite electrodes was evaluated, demonstrated much enhanced properties compared to bare GeP3 and also GeP3/carbon black electrode. High reversible capacity of 781 mAh/g was achieved by GeP3/PPC-950 at 0.05 A/g. At higher current density of 2 A/g, the capacity can maintain at 360 mAh/g, 46% of the value that obtained at 0.05 A/g. The correlation between the structure of carbon and battery performance was discussed. The improvement in battery performance can be attributed to suppressed volume expansion and good conductive network of the GeP3/PPC composite, which affected by P doping level and O content of PPC.